78.2k views
2 votes
8)
Solve using the Quadratic Formula.

x2 + 3x - 5 = 0

User Bill TP
by
4.7k points

1 Answer

2 votes

Explanation:


x^(2) + 3x - 5

For any quadratic equation
ax^(2) + bx + c = 0, the quadratic formula is as follows:


\frac{-b \pm \sqrt{b^(2) - 4ac}}{2a}

From the given quadratic equation, we know that
a = 1,
b = 3 and
c = -5. Plugging in these values into the quadratic formula gives us the following:


\frac{-(-3) \pm \sqrt{(3)^(2) - 4(1)(-5)}}{2(1)}


(3 \pm √(9 + 20))/(2)


(3 \pm √(29))/(2)

User Flobesst
by
4.8k points